Parkinsonism as an atypical primary presentation of sporadic Creutzfeldt-Jakob diseaseParkinsonism As The Atypical Primary Presentation Of Sporadic Creutzfeldt-Jakob Disease: A Case Report - Mehrdel, Roghieye; Mozhdehipanah, Hossein; Paybast, Sepideh (Universa Medicina, 2019)
BackgroundCreutzfeldt - Jakob disease (CJD) is a rare prion-related neurodegenerative disease with a rapid progression and almost definitely fatal outcome. The most common manifestation is rapidly progressive dementia with gait ataxia and visual disturbance. However there are a few reports of patients with atypical features as the initial presentation that later developed to typical characteristics in the course of the disease. Additionally there are variants of CJD in which the primary manifestation might be challenging as the ones presenting with psychiatric complaints accompanied by sensory impairment. To our knowledge, the prognosis in the classical form of the disease is poorer with a rapid deterioration leading to death. Here we aimed to focus on the diverse presentations of sporadic CJD (sCJD) especially in the early stages which might cause a conflict for proper diagnosis.Case descriptionThe patient was a 62-year old man presenting to our referral clinic with progressive gait disturbance and bradykinesia. Based on the initial examination, atypical parkinsonism was diagnosed. However, over two weeks the patient developed an acute confusional state with involuntary movement. The second examination was highly suggestive of sCJD which was confirmed by the paraclinical assessments.ConclusionSporadic CJD is a rare neurodegenerative disease with distinctive characteristics. However, there are reports of various manifestations of the disease. The present report indicates the diverse presentations of sCJD.